Revenue Diversification, Performance and Bank Risk: Evidence from Indonesia - Hafidiyah, Mutiara Nur; Trinugroho, Irwan (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2016)
This paper examines the effect of revenue diversification on bank performance and bank risk by studying 101 conventional commercial banks in Indonesia over the period of 2010-2014 resulting in 505 observations. By employing panel least square technique, our results show that revenue diversification negatively affects bank performance. Moreover, it is found that diversified banks are riskier than specialized banks. The risk is diminished when state-owned banks diversify their business. Joint venture banks are riskier than other banks when they engage in non-interest income activities.